Disulfiram in glioma: Literature review of drug repurposing - Shiyu Zhong; Shengyu Liu; Xin Shi; Xin Shi; Xudong Zhang; Kunhang Li; Guojun Liu; Lishuai Li; Shanwei Tao; Bowen Zheng; Weichen Sheng; Ziyin Ye; et al. (Frontiers Media S.A., 2022)
Gliomas are the most common malignant brain tumors. High-grade gliomas, represented by glioblastoma multiforme (GBM), have a poor prognosis and are prone to recurrence. The standard treatment strategy is tumor removal combined with radiotherapy and chemotherapy, such as temozolomide (TMZ). However, even after conventional treatment, they still have a high recurrence rate, resulting in an increasing demand for effective anti-glioma drugs. Drug repurposing is a method of reusing drugs that have already been widely approved for new indication. It has the advantages of reduced research cost, safety, and increased efficiency. Disulfiram (DSF), originally approved for alcohol dependence, has been repurposed for adjuvant chemotherapy in glioma. This article reviews the drug repurposing method and the progress of research on disulfiram reuse for glioma treatment.